2021
DOI: 10.1002/ehf2.13287
|View full text |Cite
|
Sign up to set email alerts
|

Self‐care perception and behaviour in patients with heart failure: A qualitative and quantitative study

Abstract: Background and objective Self-care strategies in heart failure (HF) are effective for disease management, yet adherence in many patients is inadequate. Reasons are presumably multifactorial but remain insufficiently investigated; thus, we aimed to analyse self-care adherence and associated factors in outpatients with HF. Methods and results To measure self-care levels and explore barriers and facilitators to self-care adherence in patients with HF, quantitative study using the European Self-Care Behaviour Scal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
1
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 41 publications
4
44
1
1
Order By: Relevance
“…Social expectations regard working as role responsibility within socialization, while body conditions have prevented better working activities due to time of shifts, working places, and work intensity. In line with the findings in a mixed-methods study ( 31 ), patients with heart failure continued to work due to socially based values until they were highly symptomatic.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Social expectations regard working as role responsibility within socialization, while body conditions have prevented better working activities due to time of shifts, working places, and work intensity. In line with the findings in a mixed-methods study ( 31 ), patients with heart failure continued to work due to socially based values until they were highly symptomatic.…”
Section: Discussionsupporting
confidence: 72%
“…According to Whitehead et al, surveillance and support from families could create a context of self-management and promote adherence to daily self-care ( 44 ). Conversely, some participants would not like to be accompanied by others only if when they perceived they were in an extremely severe body condition, for some were reluctant to seek help and some were reluctant to become a burden ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…But generally, our findings are consistent with other reports that showed the adherence to monitoring body weight was poor, while adherence to prescribed medications was good in the majority of them [12,13]. Furthermore, binary logistic regression analysis indicated that gender, marital status, educational level, and comorbidity weren't significantly associated with adherence to self-care recommendations this was contrary to the study conducted in HF Slovenian patients [21].…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, unfavorable attitudes about specific behaviors (eg, diet, exercise, medication) as difficult, not beneficial, or harmful may serve as barriers to effective self-care. 77 To date, researchers exploring attitudes about HF self-care have used mostly qualitative methods to describe how attitudes influence self-care, 77 including adherence to diet, 78 medication, 50 , 79 and treatment-seeking delays for symptom management. 50 , 74 , 80 Results confirm that HF self-care is more likely when attitudes are favorable.…”
Section: Problem Person and Environmental Factorsmentioning
confidence: 99%